IMPROVING TEACHERS' COMPETENCE IN IDENTIFYING STUDENTS' LEARNING STYLES - Nurkholis Nurkholis; Agnita Prihandini; Ainun Husna; Anggi Eka Pratiwi; Anggun Nurani; Anita Pipit Aziz (Jurnal Abdisci, 2026)
Background. One of the key factors that determine the success of learning is the teacher's ability to identify students' learning styles. Each individual has a unique learning style—such as visual, auditory, or kinesthetic—which influences how they absorb, process, and understand information. However, many teachers, especially at the elementary school level, still face challenges in recognizing and adapting their teaching methods to meet students' learning needs.Aims. The training program for enhancing teachers' competence in identifying students' learning styles aims to improve teachers' understanding and ability to implement teaching strategies that align with the individual needs of students. The training materials covered an introduction to four types of learning styles (visual, auditory, kinesthetic, and verbal) and effective methods for identifying these styles, including diagnostic assessments and direct observation. Result. The evaluation results indicated a significant improvement in participants' understanding and skills, supported by questionnaire data and direct observations. This training provided new insights and practical strategies for teachers to create more effective and adaptive learning experiences tailored to students' needs.Conclusion. This training provided new insights and practical strategies for teachers to create more effective and adaptive learning experiences tailored to students' needs.Implementation.This training was conducted at SDN Pelandakan 1, targeting teachers from SDN Pelandakan 1 and SDN Pelandakan 2, involving 45 to 50 participants. The training methods included interactive lectures, practical simulations, and reflection-based evaluations.